PENINGKATAN PRESTASI BELAJAR PKn DENGAN MODEL COOPERATIVE LEARNING MENGGUNAKAN MEDIA STIK BERJALAN PADA SISWA KELAS III SD NEGERI 023 KASIKAN KECAMATAN TAPUNG HULU TAHUN 2021 - Tiur Ida (EduTeach : Jurnal Edukasi dan Teknologi Pembelajaran, 2022)
The problem in this research is how to improve the learning achievement of Citizenship Education (PKn) with the Cooperative Learning model using a walking stick media for third grade students of SD 023 Kasikan.The aims of this study were (1) to increase student activity, (2) to increase teacher activity, (3) to improve student achievement through cooperative learning using a walking stick media.This research is a classroom action research conducted with 2 cycles. Each cycle consists of four stages, namely: (1) planning, (2) implementation, (3) observation, (4) reflection. The subjects of this study were third grade students of SD Negeri 023 Kasikan with a total of 28 students. Data collection instruments are observation, interviews, tests, documentation. The data was then processed using quantitative and qualitative descriptive analysis techniques.The results of this study indicate that the application of the Cooperative Learning learning model with the walking stick media has succeeded in improving the Civics learning outcomes for third grade students of SD Negeri 023 Kasikan. In each cycle of student learning activities increased, namely: the first cycle with an average value of 2.71 or 67.7% and the second cycle 3.2 or 80.5%. Student learning outcomes in the pre-test and post-test experienced an increase in the average value of pre-test 56, post-test 64, while the second cycle of pre-test was 65, post-test was 88. The percentage of mastery learning in the first cycle was 54% and the second cycle was 89%.Based on the results of this study, it can be concluded that learning Civics Education using Cooperative Learning with walking stick media for third grade students of SD Negeri 023 Kasikan can increase student activity. It is recommended that teachers can apply the Cooperative Learning learning model with stick media running on other appropriate subject matter